Hysteretic–Viscous Hybrid Damper System for Long-Period Pulse-Type Earthquake Ground Motions of Large Amplitude - Hashizume, Shoki; Takewaki, Izuru (Frontiers in Built Environment, 2020)
This paper aims to develop a hysteretic-viscous hybrid (HVH) damper system for long-period pulse-type earthquake ground motions of large amplitude. Long-period pulse-type earthquake ground motions of large amplitude have been recorded recently (Northridge 1994, Kumamoto 2016). It is well known that these ground motions could cause severe damage to high-rise and base-isolated buildings with long natural period. To mitigate the damage caused by such ground motion, a new viscous-hysteretic hybrid damper system is proposed here which consists of a viscous damper with large stroke and a hysteretic damper including a gap mechanism. A double impulse is employed as a representative of long-period pulse-type earthquake ground motions of large amplitude and a closed-form maximum response to this double impulse is derived for an elastic-plastic SDOF system including the proposed HVH system. To reveal the effectiveness of the proposed HVH system, time-history response analyses are performed for an amplitude modulated double impulse and a recorded ground motion at Kumamoto (2016). The performance comparison with the previous dual hysteretic damper (DHD) system consisting of small-amplitude and large-amplitude hysteretic dampers in parallel is also conducted to investigate the effectiveness of the proposed HVH system.